2000
DOI: 10.1385/bter:76:1:31
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Intestinal Absorption of Aluminum in Rats : Effects of Aluminum Compounds and Some Dietary Constituents

Abstract: In the present investigation, the deposition of aluminum in intestinal fragment and the appearance in blood were studied in a perfused rat intestine in situ for 1 h with several aluminum forms (16 mM). We observed that aluminum absorption was positively correlated with the theoretic affinity of aluminum and the functional groups of the chelating agent. The absorption of aluminum after ingestion of organic compounds is more important than after ingestion of mineral compounds, with the following order: Al citrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…The intestinal tract is the first barrier against Al exposure. Previous studies reported that the intestinal tract was the main storage organ for Al: forty percent of the ingested Al was found to accumulate in the intestinal mucosa [6,7]. The intestinal barrier consists of a single layer of epithelial cells and tight junction (TJ) proteins, acting as the body’s first line of defense against harmful substances, including heavy metals [8].…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal tract is the first barrier against Al exposure. Previous studies reported that the intestinal tract was the main storage organ for Al: forty percent of the ingested Al was found to accumulate in the intestinal mucosa [6,7]. The intestinal barrier consists of a single layer of epithelial cells and tight junction (TJ) proteins, acting as the body’s first line of defense against harmful substances, including heavy metals [8].…”
Section: Introductionmentioning
confidence: 99%
“…Increased aluminium concentrations were found in the brains of deceased Alzheimer's patients. Other studies, however, have been unable to find definite indications supporting the hypothesis that aluminium plays a causative role in Alzheimer's disease or causes pathological alterations in vivo in the species studied [14][15][16][17][18][19][20].…”
Section: Introduction and Objectivementioning
confidence: 99%
“…Aluminium acts as a pro oxidant and on continuous exposure starts accumulation in cortex, hypothalamus and different parts of brain, where it induces the formation of reactive oxygen species (ROS) and result in oxidative damage. 4 Aluminium also promotes amyloidosis β peptide formation and amyloidosis which leads to Alzheimer's disease. Increased accumulation of AlCl 3 in brain will affect the slow and fast axonal transports and cause neuro-inflammation and synoptic structural abnormality resulting in neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%